The Simcup Morocco: Exploration of the concept, innovative pedagogical relevance, and perspectives - Mohamed El Mouhajir; Yahaya Maijimaa Tourey; Majdouline Obtel; Mohammed Mouhaoui (Educación Médica)
Introduction: The Simcup is a leading national event in the medical field, with clinical competition in terms of simulation. Here, groups of medical students from different faculties in the country participate in patient simulation scenarios, particularly in the field of emergency and disaster medicine. Our aim is to present SIMCUP Morocco in a comprehensive way. This involves describing the participation process, strategies for success, elucidating the format, stages, and timetable. In addition, we aim to provide an impartial assessment of its importance, its educational value for medical students, and its influence on their training. Materials and methods: We developed a questionnaire covering 7 key areas to assess the effectiveness of the Simcup: Teamwork, communication, debriefing, psychological aspects, overall perspectives, areas for improvement, and a bonus category. We collected responses from 120 medical students representing various faculties in Morocco. Results: A total of 120 participated in our study, with an average age between 25 and 26 years. The participation rate of virtual staff varied, with a majority indicating their presence at 47.5%. Notably, 81% of students strongly agreed with the importance of implementing simulation as an assessment modality within faculties. These results argue in favor of the relevance of Simcup and underline the superiority of simulation-based learning over traditional clinical teaching, both as a teaching method and for the evaluation of learning outcomes. Conclusion: Despite the limited number of studies investigating the comparative effectiveness of simulation-based learning versus traditional clinical teaching, our results highlight the value of simulation-based approaches in medical education. Resumen: Introducción: El Simcup es un evento nacional líder en el campo de la medicina, con competencia clínica en términos de simulación. En él, grupos de estudiantes de medicina de diferentes facultades del país participan en escenarios de simulación de pacientes, especialmente en el campo de la medicina de urgencias y catástrofes. Nuestro objetivo es presentar la SIMCUP Marruecos de forma exhaustiva. Esto implica describir el proceso de participación, las estrategias para el éxito, dilucidar el formato, las etapas y el calendario. Además, pretendemos ofrecer una evaluación imparcial de su importancia, su valor educativo para los estudiantes de medicina y su influencia en su formación. Materiales y métodos: Desarrollamos un cuestionario que cubría siete áreas clave para evaluar la eficacia del Simcup trabajo en equipo, comunicación, debriefing, aspectos psicológicos, perspectivas generales, áreas de mejora y una categoría de bonificación. Recogimos las respuestas de 120 estudiantes de medicina de varias facultades de Marruecos. Resultados: Un total de 120 participaron en nuestro estudio, con una edad media entre 25 y 26 años. La tasa de participación del personal virtual varió, siendo mayoritaria en un 47,5%. Cabe destacar que el 81% de los estudiantes se mostró muy de acuerdo con la importancia de implementar la simulación como modalidad de evaluación dentro de las facultades. Estos resultados argumentan a favor de la relevancia del Simcup y subrayan la superioridad del aprendizaje basado en la simulación sobre la enseñanza clínica tradicional, tanto como método de enseñanza como para la evaluación de los resultados del aprendizaje. Conclusiones: A pesar del limitado número de estudios que investigan la eficacia comparativa del aprendizaje basado en la simulación frente a la enseñanza clínica tradicional, nuestros resultados destacan el valor de los enfoques basados en la simulación en la educación médica.